Addressing Islamism Through Fiqh Al-Bi'ah: an Educational Approach in The Miftahul Ula Islamic Boarding School, Kertosono, Nganjuk - Maslachah Maslachah; Ghazza Jaudat Fastmadhi; Nazwa Svenska Aulia Fastmadhi; Deddi Fasmadhy Satiadharmanto (Siber Nusantara of Community Service Review, 2024)
This study explores the implementation of Islamic religious education, especially through the lens of Fiqh Al-Bi'ah, as a basic strategy to overcome radicalism in Pesantren Miftahul Ula Kertosono Nganjuk. Fiqh Al-Bi'ah, which focuses on environmental and cleanliness jurisprudence, becomes a comprehensive framework to instill the values ??of cleanliness, sanctity, and environmental management among students.This study investigates how this educational approach contributes to shaping a culture that is resistant to the ideology of Islamism in the pesantren community. By examining the practical application and impact of Fiqh Al-Bi'ah, this study aims to provide insight into effective educational strategies in dealing with Islamism in Islamic educational environments.